Active Learning: Monopoly as a Media in Teaching Grammar for Eight Grader Students - Ananda Dewi Lestari; Ary Setya Budhi Ningrum (Journal of Languages and Language Teaching, 2022)
The diversity in English performance is quite prominent when viewed from students' grammatical competence. For this reason, grammar learning innovation is needed so that student mastery improves. This study aims to investigate the effectiveness of using board game Engpoly (English Monopoly) in learning grammar for eight-grader students. It also provides reflection on student learning strategies in studying grammar. The design used a quasi-experimental design. For collecting the data, the researchers applied post-test and pre-test as research instruments. It involved two classes as a control group and an experimental group. The ANCOVA test results showed the significance of using Engpoly media in learning grammar. The finding also demonstrated that the use of fun media in the form of games can increase students' interest in learning grammar which was initially considered a very boring lesson by most students. It also encouraged student's active learning. This media has been proven to relate between the characteristics of eighth-grade students at junior high school with the appropriate grammar learning strategies they need. Since the use of Engpoly in grammar learning has a significant contribution, this study recommends that English teachers can develop Engpoly media for teaching grammar not only to eighth-graders but also to several other levels of english proficiency.